Bilingual interactional contexts predict executive functions in older adults - YANG, Hwajin (Institutional Knowledge at Singapore Management University, 2023)
Drawing on the adaptive control hypothesis, we examined whether older adults' bilingual interactional contexts of conversational exchanges would predict important indices of executive functions (EF). We assessed participants' engagement in each bilingual interactional context - single-language, dual-language, and dense code-switching - and their performance on a series of nonverbal EF measures. Sixty-nine healthy older adults (M-age = 70.39 years; ages 60-93) were recruited from local community centers. We found that the dense code-switching context was associated with enhanced overall EF, but not individual facets of EF (inhibitory control, shifting, and updating). These findings held true when we controlled for a host of covariates. Our findings shed light on aging bilinguals' interactional contexts as crucial bilingual experiences that modulate overall EF. Given that bilingualism is a multidimensional construct, rather than a unidimensional variable, our study underscores the importance of more fine-grained operationalisation of bilingualism when studying its impacts on EF.